The age of doubt : tracing the roots of our religious uncertainty - Lane, Christopher, 1966- (Yale University Press, 2011)
The Victorian era was the first great "Age of Doubt" and a critical moment in the history of Western ideas. Leading nineteenth-century intellectuals battled the Church and struggled to absorb radical scientific discoveries that upended everything the Bible had taught them about the world. In The Age of Doubt, distinguished scholar Christopher Lane tells the fascinating story of a society under strain as virtually all aspects of life changed abruptly. In deft portraits of scientific, literary, and intellectual icons who challenged the prevailing religious orthodoxy, from Robert Chambers and Anne Brontë to Charles Darwin and Thomas H. Huxley, Lane demonstrates how they and other Victorians succeeded in turning doubt from a religious sin into an ethical necessity. The dramatic adjustment of Victorian society has echoes today as technology, science, and religion grapple with moral issues that seemed unimaginable even a decade ago. Yet the Victorians' crisis of faith generated a far more searching engagement with religious belief than the "new atheism" that has evolved today. More profoundly than any generation before them, the Victorians came to view doubt as inseparable from belief, thought, and debate, as well as a much-needed antidote to fanaticism and unbridled certainty. By contrast, a look at today's extremes--from the biblical literalists behind the Creation Museum to the dogmatic rigidity of Richard Dawkins's atheism--highlights our modern-day inability to embrace doubt